Recurrent Bilateral Occipital Infarct with Cortical Blindness and Anton Syndrome - Kwong Yew, Kiu (Hindawi Publishing Corporation, 2014)
Bilateral cortical blindness and Anton syndrome, are most commonly caused by ischaemic stroke. In this condition, patients have loss of vision but deny their blindness despite objective evidence of visual loss. We report a case of a patient with multiple cardiovascular risk factors who developed recurrent bilateral occipital lobe infarct with Anton syndrome. A suspicion of this condition should be raised when the patient has denial of blindness in the presence of clinical and radiological evidence of occipital lobe injury. Management of this condition should focus on the underlying cause, in which our patient requires secondary stroke prevention and rehabilitation.